Nursery fertilisation affects morphological quality attributes of pot-grown Engkabang jantong (Shorea macrophylla de Vr.) seedlings - Mugunthan, Perumal; Mohd Effendi, Wasli; Latifah, Omar; Jonathan, Lat (2023)
One of the key elements of a successful forest restoration programme is a better understanding and application of nursery cultural regimes to increase seedling quality with high survival capability and optimal development potential. Thus, a nursery experiment was investigated to examine the effects of controlled-instant release fertiliser (CIRF) on the morphological quality attributes of Engkabang jantong (Shorea macrophylla de Vr.) seedlings. Following standard forest nursery procedures, the pots were filled with a 1:1 mixture of topsoil and sand (v:v). Either a chemical fertiliser (CF, N: P: K = 10: 26: 10) or a blend of 360-day (80% elution of the ingredients at 25°C) controlled-instant release fertiliser (CIRF, N: P: K = 10: 26: 10) was applied at the rate of 5 g per pot. At the end of the nursery growing season, the findings revealed that the survival rate and morphological quality attributes, particularly for the shoot height, root collar diameter, relative growth rate of shoot height, and sturdiness quotient of S. macrophylla seedlings treated with CIRF were significantly higher than those treated with CF. Notwithstanding, both treatments produced sub-optimal quality seedlings that met the standard criteria for a balanced root-to-shoot ratio (R: S < 2). Morphological and physiological characteristics of seedlings must be integrated into the stock quality evaluation to provide a more accurate assessment of the fitness of seedlings to become established for field planting.